An Alliance of Gel-Based and Gel-Free Proteomic Techniques Displays Substantial Insight Into the Proteome of a Virulent and an Attenuated Histomonas meleagridis Strain - Monoyios, Andreas; Hummel, Karin; Nöbauer, Katharina; Patzl, Martina; Schlosser, Sarah; Hess, Michael; Bilic, Ivana (Frontiers in Cellular and Infection Microbiology, 2018)
The unicellular protozoan Histomonas meleagridis is notorious for being the causative agent of histomonosis, which can cause high mortality in turkeys and substantial production losses in chickens. The complete absence of commercially available curative strategies against the disease renders the devising of novel approaches a necessity. A fundamental step toward this objective is to understand the flagellate's virulence and attenuation mechanisms. For this purpose we have previously conducted a comparative proteomic analysis of an in vitro cultivated virulent and attenuated histomonad parasite using two-dimensional electrophoresis and MALDI-TOF/TOF. The current work aimed to substantially extend the knowledge of the flagellate's proteome by applying 2D-DIGE and sequential window acquisition of all theoretical mass spectra (SWATH) MS as tools on the two well-defined strains. In the gel-based experiments, 49 identified protein spots were found to be differentially expressed, of which 37 belonged to the in vitro cultivated virulent strain and 12 to the attenuated one. The most frequently identified proteins in the virulent strain take part in cytoskeleton formation, carbohydrate metabolism and adaptation to stress. However, post-translationally modified or truncated ubiquitous cellular proteins such as actin and GAPDH were identified as upregulated in multiple gel positions. This indicated their contribution to processes not related to cytoskeleton and carbohydrate metabolism, such as fibronectin or plasminogen binding. Proteins involved in cell division and cytoskeleton organization were frequently observed in the attenuated strain. The findings of the gel-based studies were supplemented by the gel-free SWATH MS analysis, which identified and quantified 42 significantly differentially regulated proteins. In this case proteins with peptidase activity, metabolic proteins and actin-regulating proteins were the most frequent findings in the virulent strain, while proteins involved in hydrogenosomal carbohydrate metabolism dominated the results in the attenuated one.